Stability of cobalt–carbon high temperature fixed points doped with iron and platinum. (24th March 2015) - Kňazovická, L; Lowe, D; Machin, G; Davies, H; Rani, A
Abstract: High temperature fixed points (HTFPs) are stable and repeatable and make comparison of temperature scales possible at a level of uncertainty not previously possible. However, they potentially lack objectivity if the fixed-point temperature is known. Five HTFPs were constructed, one pure Co–C, two Co–C doped with Fe and two Co–C doped with Pt of differing concentrations. The candidate dopants were identified through thermochemical modelling as likely to give maximum temperature shift with minimum increase in melting range. The temperature differences of the doped systems from the pure system were determined and it was found that the addition of Fe depressed the melting temperature and the addition of Pt elevated the melting temperature, qualitatively in line with the thermochemical modelling. The higher concentration doped HTFPs were then aged for approximately 100 h with continuous melting–freezing cycles and the difference to the undoped Co–C HTFP remeasured. These differences were found to agree with those of the unaged results within the measurement uncertainties, confirming artefact stability. It is clear that the doping of HTFPs is a powerful way of constructing stable and reliable high temperature scale comparison artefacts of unknown temperature.